REGULATORY AND LEGAL PROVISION OF THE APPLICATION IN UKRAINE OF A GENDER ORIENTED APPROACH IN THE BUDGET PROCESS - Tsiupa, O.P.; Kondur, O.S. (The actual problems of regional economy development, 2023)
The article examines the main regulatory and legal acts in the field of applying a gender-oriented approach in the budget process in Ukraine, because according to the authors' beliefs, the efficiency, effectiveness and fairness of the distribution of budget funds and the approval of the policy of equal rights and opportunities for women and men depend on the clarity of its formation and/ or their groups. In the scientific literature, there is no in-depth study of the problem of regulatory and legal support for the application of a gender-oriented approach in the budget process, therefore, the analysis of the legislation as a separate study is relevant. The article analyzes the principles of the State Finance Management Reform Strategy for 2022-2025, state regional development strategies for 2021-2027, and ensuring equal rights and opportunities for women and men until 2030. It is noted that the definition of the goals and objectives in the strategic documents of Ukraine regarding the application of a gender-oriented approach in the budget process indicates the recognition of the effectiveness of this tool and its further application in order to increase the efficiency, effectiveness and fairness of the use of budget funds and the provision of quality public services taking into account the needs of women, men and/or their groups, and generally increasing the level of socio-economic development of our state. The results of the analysis of normative and legal acts regulating budget relations in Ukraine indicate the development, albeit slow, of legislative support for the use of a gender-oriented approach in the budget process at the state and local levels. But still there are problems that need to be solved in order to ensure the end-to-end application of a gender-oriented approach in the budget process. In particular, to include a gender-oriented approach in the Budget Code of Ukraine in order to ensure the mandatory, systematic and sustainable use of a gender-oriented approach in the budget process by all participants in the budget process at the state and local levels. And also, to include norms for the application of a gender-oriented approach to regulatory and legal acts that regulate not only the process of budget planning, but also the process of implementation and reporting on the implementation of state and local budgets, which will enable the Government and the public to monitor the amount of budget funds that are directed to ensuring gender equality.